Human Rights in Indonesia's Constitution: Human Rights Violations in Sexual Violence - Asit Defi Indriyani; Rachma Dini Fitria (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
Human Rights (HAM) are basic rights that are owned by every human being which is natural because it is a gift from God and is inherent in every human being that must be guarded, protected and respected. Indonesia as a constitutional state of law should place human rights in the applicable constitution. In Indonesia, sexual violence is still an important issue because the rate of cases is still high every year. Sexual violence is a form of violation of human rights. The purpose of this study is to analyze sexual violence which is considered a violation of human rights. The type of research in this writing is normative or library research, namely researching by examining various library sources related to the topic of discussion. The results of this study are that acts of violence against women are considered a violation of human rights and have been agreed at the world conference on human rights in Vienna in 1993. In the constitution in Indonesia, it has been regulated in Chapter XA article 28, some of which are related to the right to be free from treatment and get protection from discrimination. For a child, the right to survive, grow and develop, and receive protection from violence and discrimination is also regulated. Sexual violence must be seen from the elements of crimes against human rights because it is related to human dignity.